2021
DOI: 10.31235/osf.io/rpfza
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rise of income and the demise of class and social status? A systematic review of measures of socio-economic position in stratification research

Abstract: How we measure social position is vital to our ability to account for different aspects – imagined or real – of the stratification order. This research note surveys applied research and quantifies differences in the way researchers study stratification. It analyses all research articles published from 2015-2019 in the five most-cited sociological journals and ISA RC28's official publication. We focus on empirical articles with a substantive focus on occupation-based stratification. Empirically, we observe a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Moreover, the encouraging results of previous validation studies and the four desirable properties of these class schemes identified in this study constitute compelling arguments against such a drastic solution. The overriding dominance of EGP-like schemes in class analysis in recent years (Barone et al 2020) testifies to their persistent popularity among empirical researchers. Based on our results, we therefore identify three pragmatic ways to proceed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the encouraging results of previous validation studies and the four desirable properties of these class schemes identified in this study constitute compelling arguments against such a drastic solution. The overriding dominance of EGP-like schemes in class analysis in recent years (Barone et al 2020) testifies to their persistent popularity among empirical researchers. Based on our results, we therefore identify three pragmatic ways to proceed.…”
Section: Discussionmentioning
confidence: 99%
“…Even according to Erikson and Goldthorpe themselves ESEC should supersede EGP (personal communication). However, EGP continues to prevail in current stratification research (Barone et al 2020). In the absence of validation studies contrasting the two schemes other than the volume that introduced ESEC (Rose and Harrison 2010), there is little justification for either choice.…”
Section: Figure 3: Egp-like Class Scheme Assignment Procedures and Employment Relations Measuresmentioning
confidence: 99%
“…Goldthorpe (Rose & Harrison, 2010: 10-23) (Barone et al, 2021;Birkelund, Goodman, & Rose, 1996;Evans, 1992Evans, , 1996Evans & Mills, 1998;Rose & Harrison, 2010). Sie (oder eine ihrer vielen nationalen Varianten) bilden damit das am häufigsten validierte und angewandte Klassenschema in soziologischen Ungleichheitsanalysen (Barone et al, 2021). (Rose & Harrison, 2010: 21).…”
unclassified